(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
This study aimed to estimate the abundance and diversity of phytoplankton at different depth of water columns in Northern Bay of Bengal, Bangladesh. Samples were collected from 24 stations using Niskin water sampler from 0 to 250 m depths in four different cruises from January, 2017 to January, 2018 with the collaboration of Bangladesh Navy. Before sample identification, the samples were subjected to preservation using Lugol’s solution. A total of 70 phytoplankton species were identified of which Bacillariophyceae, Dinophyceae and Chlorophyceae covered 74.28%, 21.42% and 4.28% of species, respectively. The average phytoplankton density was 12,238±7,281 cells/L. Results showed phytoplankton abundance and distribution was comparatively lower in higher water depth than surface water. The highest phytoplankton abundance (39,342 cells/L) was recorded at surface water and the lowest abundance (16 cells/L) was observed in 200 m depth. Phytoplankton abundances significantly reduced at higher water depths (p < 0.05) which might be associated with higher light and nutrients availability at surface water and mixed layer depth. However, there was weak negative correlation since r = - 0.33. Phytoplankton abundance was also varied from station to station at similar water depth. Species richness was the highest in surface water. In this study, estimated Shannon-Wiener index was 0.58 that represented phytoplankton was moderately distributed at surface water than higher depth. The findings of the present study might be used as a baseline study to understand the phytoplankton community of the Northern Bay of Bengal which directly and/or indirectly help to manage existing ecosystem and sustainable fisheries of the Bay of Bengal. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 10(1), 2021, P 11-21